Writing to Declare the Reception of the Poet Sergio Mansilla Torres to the Chilean Academy of Language (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Welcome speech to the new academic, as the corresponding member of the Chilean Academy of Language, Mr. Sergio Mansilla Torres. The recipient, the poet Delia Domínguez, is a full member of the Chilean Academy of Language. The entrance ceremony to the Academy was held in Osorno, Cultural Center of the Illustrious Municipality of Osorno, on June 1, 2001.